Strategi Pengemasan Wisata Heritage di Desa Wisata Kerta, Kecamatan Payangan, Kabupaten Gianyar, Bali - Dinov Sambadi Adistria Laksana; I Nyoman Sukma Arida (JURNAL DESTINASI PARIWISATA, 2019)
Tourism is the largest and fastest growing industry in the world. Tourism in one of the most important sector and has a significant influences in the economic development of the country. Tourism contribution is considered important for economic growth in Indonesia, because in addition to bring in foreign exchange, also felt able to open a new job for the community. Tourim in Bali has developed quite rapidly, tourism potentials in Bali has been developed well enough, so that it can be enjoyed by tourists, which became a leading tourist attraction in Bali that is nature tourism and cultural tourism. This research focuses on the planning and strategy of the packaging of heritage tourism products in Kerta Tourism Village in order to improve the local economy, considering that Kerta Tourism Village has so many heritage tourism potential that has not been developed yet. This research is expected to benefit local communities and Gianyar Government in adding data, as preliminary data, and consideration data for further in-depth research. This research has a scope that is limited to two variables, that is identifying the heritage tourism potential owned by Kerta Tourism Village and compile a strategy to package heritage tiourism in Kerta Tourism Village. The data sources used are primary data obtained from interviews with the informants, observations, and documentation in Kerta Tourim Village, and the secondary data is obtained from various books used as the theoretical basis to supporting the research. Based on the results obtained, in Kerta Tourism Village there are many tourism potentials that can be developed into a tourism attraction, one of which is heritage tourism that can be combined with cycling tourism activities and certainly useful for local people and tourists. Keywords: Heritage Tourism, Cycling Tourism, Kerta Tourism Village.